Electrode assembly and secondary battery including same
Patent Information
- Application Number
- JP2024544501
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-20
- Filing Date
- 2023-04-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-04-20
AI Technical Summary
【0024】 本発明の一実施形態によると、電極組立体の最外層に片面電極を適用するが、この場合、片面電極の製造時に適用される電極用フィルムの孔隙率を調節し、また前記電極用フィルムと集電体とのラミネーション時に電極用フィルムの圧延率を制御することで、30%以下の孔隙率を有する電極層を備えることとなり、エネルギー密度が最大になり、カール特性が向上した電極組立体、及びこれを含む二次電池を提供することができる。
Smart Images

Figure 2025505534000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode assembly and a secondary battery including the same, and more particularly, to an electrode assembly having high energy density and excellent bending properties, and a secondary battery including the same.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0049212, filed on April 20, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]
[0003] Due to the rapid increase in the use of fossil fuels, the demand for alternative and clean energy is increasing, and one of the most actively researched fields is the field of power generation and storage using electrochemistry. Currently, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and the field of its use is gradually expanding. Lithium secondary batteries, a representative example of such secondary batteries, are not only used as an energy source for mobile devices, but are also being used as a power source for electric vehicles and hybrid electric vehicles that can replace vehicles that use fossil fuels such as gasoline and diesel vehicles, which are one of the main causes of air pollution, and their field of use is expanding to include auxiliary power sources for grids.
[0004] In order to maximize the energy density of such secondary batteries, attempts have been made to apply a single-sided electrode to the outermost layer of a conventional full cell.
[0005] However, in the case of single-sided electrodes, the electrode is more likely to bend, i.e., curl, than in the case of double-sided electrodes. When single-sided electrodes with large curvature are used, there is a problem in that defects are more likely to occur during the assembly process.
[0006] Therefore, there is a pressing need to develop an electrode assembly that can solve these problems. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made to solve the above problems, and an object of the present invention is to provide an electrode assembly having a maximized energy density and improved curl characteristics, and a secondary battery including the electrode assembly. [Means for solving the problem]
[0008] In order to solve the problems of the present invention, according to one aspect of the present invention, an electrode having the following embodiment is provided.
[0009] According to a first embodiment, there is provided an electrode assembly including a mono-cell group including one or more mono-cells, a single-sided electrode laminated on at least one of the upper and lower outermost sides of the mono-cell group, and a separator interposed between the mono-cell group and the single-sided electrode, the single-sided electrode including a current collector and an electrode layer only on one side of the current collector, the porosity of the electrode layer being 30% or less, and the curl of the single-sided electrode being 30 mm or less.
[0010] According to a second embodiment, in the first embodiment, the group of mono-cells may include one mono-cell, or may include two or more mono-cells stacked together.
[0011] According to a third embodiment, in the first or second embodiment, a half cell may be further interposed between the mono-cell group and the unit electrode.
[0012] According to the fourth embodiment, in any of the first to third embodiments, the difference between the porosity of the electrode layer of the single-sided electrode and the porosity of the electrode layer of the other electrode opposite the single-sided electrode may be 5% or less.
[0013] According to a fifth embodiment, in any one of the first to fourth embodiments, the single-sided electrode comprises a current collector and an electrode layer located on the current collector and containing an active material and a binder, and the binder can be fibrous to bind the active material.
[0014] According to a sixth embodiment, in the fifth embodiment, the electrode layer may include an active material, a conductive material, and a binder.
[0015] According to a seventh embodiment, in the fifth or sixth embodiment, the binder may include polytetrafluoroethylene (PTFE).
[0016] According to the eighth embodiment, in the sixth or seventh embodiment, the content of the active material may be 80 to 98 parts by weight, the content of the conductive material may be 0.5 to 10 parts by weight, and the content of the binder may be 0.5 to 5 parts by weight.
[0017] According to a ninth embodiment, in any one of the fifth to eighth embodiments, the electrode current collector may further include a conductive primer layer on at least one surface thereof.
[0018] According to a tenth embodiment, in any one of the fifth to ninth embodiments, the electrode layer can be derived from a film for a dry electrode.
[0019] According to an eleventh embodiment, in any of the first to tenth embodiments, the single-sided electrode may be manufactured by a manufacturing method including the steps of: producing a mixture containing an active material and a binder; kneading the mixture at a temperature in the range of 70°C to 200°C and under a pressure equal to or higher than normal pressure to produce a mixture lump; pulverizing the mixture lump to obtain a mixed powder for an electrode; feeding the mixed powder for an electrode between a plurality of rolls and calendaring it to form a film for an electrode; and laminating the film for an electrode onto a current collector.
[0020] According to the twelfth embodiment, in the eleventh embodiment, the step of kneading to prepare a mixture mass can be carried out in a kneader under a pressure equal to or higher than normal pressure.
[0021] According to the thirteenth embodiment, in the eleventh or twelfth embodiment, the rolling ratio of the electrode film in the laminating step may be 10% or less.
[0022] According to a fourteenth embodiment, there is provided a secondary battery comprising the electrode assembly according to any one of the first to thirteenth embodiments.
[0023] According to a fifteenth embodiment, there is provided an energy storage device including the secondary battery according to the fourteenth embodiment as a unit battery. Effect of the Invention
[0024] According to one embodiment of the present invention, a single-sided electrode is applied to the outermost layer of an electrode assembly. In this case, the porosity of an electrode film applied during the manufacture of the single-sided electrode is adjusted, and the rolling ratio of the electrode film is controlled during lamination of the electrode film and a current collector, thereby providing an electrode layer having a porosity of 30% or less. This maximizes energy density and improves curl properties, and provides a secondary battery including the electrode assembly.
[0025] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited only to the matters described in the drawings. [Brief description of the drawings]
[0026] [Figure 1] 1 is a schematic diagram of an electrode according to one embodiment of the present invention. [Diagram 2] Schematic diagram for calculating the QBR value of the electrode layer. [Figure 3A]4A to 4C are schematic diagrams illustrating a manufacturing process of an electrode film for an electrode applied to an electrode assembly according to an embodiment of the present invention. [Figure 3B] 4A to 4C are schematic diagrams illustrating a manufacturing process of an electrode film for an electrode applied to an electrode assembly according to an embodiment of the present invention. [Figure 4] 4A to 4C are schematic diagrams illustrating an electrode lamination process for a double-sided electrode applied to an electrode assembly according to an embodiment of the present invention. [Diagram 5] 3A to 3C are schematic diagrams illustrating an electrode lamination process for a single-sided electrode applied to an electrode assembly according to an embodiment of the present invention. [Figure 6] 1 is a schematic diagram of a conventional electrode assembly in which double-sided electrodes are located on the outermost layer. [Figure 7] 1 is a schematic diagram of an electrode assembly in accordance with an embodiment of the present invention, in which a single-sided electrode is located on the outermost layer. [Figure 8] 1 is a schematic diagram of an electrode assembly in accordance with an embodiment of the present invention, in which a single-sided electrode is located on the outermost layer. [Figure 9] Photographs showing curl measurement results for the single-sided electrode of Example 2. [Figure 10] Photographs showing curl measurement results for a single-sided electrode of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The present invention will now be described in more detail for the sake of understanding.
[0028] The terms and words used in this specification and the claims are not to be interpreted limited to their ordinary and dictionary meanings, but are to be interpreted in a meaning and concept that corresponds to the technical idea of the present invention, based on the principle that the inventor himself can appropriately define the concept of the term in order to explain the invention in the best possible way.
[0029] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. Unless otherwise clearly indicated in the context, the singular expression includes the plural expression.
[0030] Also, throughout the specification, when a part is said to "comprise" a certain element, this means that it can further include other elements, rather than excluding other elements, unless specifically stated to the contrary.
[0031] According to one aspect of the present invention, there is provided an electrode assembly including a mono-cell group including one or more mono-cells, a single-sided electrode laminated on at least one of the upper and lower outermost sides of the mono-cell group, and a separator interposed between the mono-cell group and the single-sided electrode, the single-sided electrode including a current collector and an electrode layer only on one side of the current collector, the porosity of the electrode layer being 30% or less, and the curl of the single-sided electrode being 30 mm or less.
[0032] According to one embodiment of the present invention, the group of mono-cells may include one mono-cell or may include two or more mono-cells stacked together.
[0033] Here, the mono cell refers to a unit assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, and both the positive electrode and the negative electrode are double-sided electrodes, i.e., electrodes including a current collector and electrode layers on both sides of the current collector.
[0034] According to an embodiment of the present invention, a half cell may be further interposed between the mono-cell group and the unit electrode. Here, the half cell refers to a unit assembly having only one of a positive electrode and a negative electrode as an electrode, and the electrode of the half cell is a double-sided electrode having electrode layers on both sides of a current collector.
[0035] When the mono-cell group includes two or more stacked mono-cells, a separator may be interposed between adjacent mono-cells, and when a half-cell is further interposed between the mono-cell group and a unit electrode, a separator may be interposed between the mono-cell group and the half-cell and between the half-cell and the unit electrode.
[0036] According to one embodiment of the present invention, the electrode assembly may be configured by stacking in the order of "mono-cell group / separator / single electrode", or may be configured by stacking in the order of "mono-cell group / separator / half-cell (double-sided electrode) / separator / single electrode", or may be configured by stacking in the order of "single electrode / separator / mono-cell group / separator / single electrode", or may be configured by stacking in the order of "single electrode / separator / mono-cell group / separator / half-cell (double-sided electrode) / separator / single electrode", or may be configured by stacking in the order of "single electrode / separator / half-cell (double-sided electrode) / mono-cell group / separator / half-cell (double-sided electrode) / separator / single electrode".
[0037] 6 is a schematic diagram of an electrode assembly 300 in which a conventional double-sided electrode is disposed on the outermost side. The electrode assembly 300 includes a double-sided negative electrode 310 composed of a negative electrode layer 313 / a negative electrode current collector 311 / a negative electrode layer 312, a double-sided positive electrode 320 composed of a positive electrode layer 323 / a positive electrode current collector 321 / a positive electrode layer 322, and a mono-cell group including one or more mono-cells 330 each including separators 314, 315 interposed between the double-sided negative electrode 310 and the double-sided positive electrode 320, and the double-sided negative electrode 310 is disposed on the outermost side of the mono-cell group.
[0038] In such a conventional electrode assembly 300, the outermost electrode layer of the outermost double-sided electrode, which does not face the electrode layers of other electrodes, cannot be actually used in a battery, and therefore, there is a problem in that the technical requirement of maximizing the energy density of a secondary battery cannot be met.
[0039] To solve this problem, there have been attempts to apply single-sided electrodes to the outermost layer, but single-sided electrodes tend to bend more than double-sided electrodes, and using single-sided electrodes with large curvatures increases the number of defects during the assembly process.
[0040] In the present invention, as described above, by adjusting the porosity of the electrode film applied when manufacturing a single-sided electrode and controlling the rolling ratio of the electrode film when laminating the electrode film and a current collector, it is possible to manufacture a single-sided electrode having an electrode layer with a porosity of 30% or less. An electrode assembly and a secondary battery in which such a single-sided electrode is applied to the outermost side can maximize the energy density and improve curl characteristics.
[0041] 7 and 8 show schematic diagrams of an electrode assembly in which a single-sided electrode is arranged on the outermost side according to one embodiment of the present invention.
[0042] The electrode assembly 400 of FIG. 7 is configured by stacking the following in this order: single electrode / separator / mono-cell group / separator / half cell (two-sided electrode) / separator / single electrode.
[0043] Specifically, the electrode assembly 400 of FIG. 7 includes a mono-cell group including one or more mono-cells 420 each including a double-sided negative electrode composed of a negative electrode layer 423 / a negative electrode current collector 421 / a negative electrode layer 422, a double-sided positive electrode composed of a positive electrode layer 428 / a positive electrode current collector 426 / a positive electrode layer 427, and separators 424, 425 interposed between the double-sided negative electrode and the double-sided positive electrode, a first single-sided positive electrode 410 composed of a positive electrode layer 416 / a positive electrode current collector 417, and a second single-sided positive electrode 430 composed of a positive electrode layer 431 / a positive electrode current collector 432, which are disposed on both outermost sides of the mono-cell group, and further includes a double-sided negative electrode (half cell) 410′ composed of a negative electrode layer 413 / a negative electrode current collector 411 / a negative electrode layer 412 between the first single-sided positive electrode 410 and the mono-cell group. At this time, separation membranes 414, 415 are interposed between the one-sided positive electrode, the two-sided negative electrode, and the mono-cell group.
[0044] The electrode assembly 500 shown in FIG. 8 is configured by stacking mono-cell group / separator / half-cell (two-sided electrode) / separator / single electrode in this order.
[0045] 8 includes a mono-cell group including one or more mono-cells 420 each including a double-sided negative electrode composed of a negative electrode layer 423 / a negative electrode current collector 421 / a negative electrode layer 422, a double-sided positive electrode composed of a positive electrode layer 428 / a positive electrode current collector 426 / a positive electrode layer 427, and separators 424, 425 interposed between the double-sided negative electrode and the double-sided positive electrode, and a single-sided positive electrode 410 arranged on one outermost side of the mono-cell group and composed of a positive electrode layer 416 / a positive electrode current collector 417, and further includes a double-sided negative electrode 410' composed of a negative electrode layer 413 / a negative electrode current collector 411 / a negative electrode layer 412 between the single-sided positive electrode and the mono-cell group. In this case, separators 414, 415 are interposed between the single-sided positive electrode, double-sided negative electrode, and mono-cell group.
[0046] According to one embodiment of the present invention, the single-sided electrode includes a current collector and an electrode layer located on the current collector and including an active material and a binder, and the binder can be fibrous to bind the active material.
[0047] The one-sided electrode may be a positive electrode or a negative electrode, and the active material may be a positive electrode active material or a negative electrode active material.
[0048] The positive electrode active material may include, but is not limited to, a lithium transition metal oxide, a lithium metal iron phosphate, a lithium nickel-manganese-cobalt oxide, an oxide in which a part of the lithium nickel-manganese-cobalt oxide is replaced with another transition metal, or two or more of these. Specifically, the positive electrode active material may include, but is not limited to, a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), a compound substituted with one or more transition metals, and a compound represented by the chemical formula Li 1+x Mn 2-x Lithium manganese oxides such as LiMnO4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, and Cu2V2O7; and vanadium oxides with the chemical formula LiNi 1-x M xO2 (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3), a Ni-site type lithium nickel oxide, and chemical formula LiMn 2-x M x O2 (where M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn), a lithium manganese composite oxide, and lithium metal phosphate LiMPO4 (where M = Fe, CO, Ni, or Mn), and lithium nickel-manganese-cobalt oxide Li 1+x (Ni a Co b Mn c ) 1-x O2 (x = 0 to 0.03, a = 0.3 to 0.95, b = 0.01 to 0.35, c = 0.01 to 0.5, a + b + c = 1), and an oxide in which part of the lithium nickel-manganese-cobalt oxide is substituted with aluminum (lithium nickel-manganese-cobalt-aluminum oxide) Li a [Ni b Co c Mn d Al e 1-f M 1 f O2 (where the above M 1 is one or more selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P and S, 0.8 ≤ a ≤ 1.2, 0.5 ≤ b ≤ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≤ e ≤ 0.1, 0 ≤ f ≤ 0.1), disulfide compounds, Fe2(MoO4)3, etc., but are not limited thereto. Specifically, the lithium nickel-manganese-cobalt-aluminum oxide may be Li[Ni 0.87 Co 0.05 Mn 0.07 Al 0.01 O2 or the like.
[0049] Also, as the negative electrode active material, carbon such as graphitizable carbon and graphite-based carbon, and Li x Fe2O3 (0 ≤ x ≤ 1), Lix WO2(0≦x≦1), Sn x Me 1-x Me' y O z Metal composite oxides such as (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1 elements, Group 2 elements, Group 3 elements, halogens of the periodic table; 0≦x≦1; 1≦y≦3; 1≦z≦8), lithium metal, lithium alloys, silicon-based alloys, tin-based alloys, silicon-based oxides such as SiO, SiO / C, and SiO2, metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5, conductive polymers such as polyacethylene, and Li-Co-Ni-based materials can be used.
[0050] According to an embodiment of the present invention, the one-sided electrode is a positive electrode, and thus the active material is specifically a positive electrode active material, more specifically, lithium transition metal oxide, lithium nickel-manganese-cobalt oxide, an oxide in which a part of the lithium nickel-manganese-cobalt oxide is substituted with Al or other transition metals, lithium iron phosphate, etc.
[0051] According to an embodiment of the present invention, the electrode layer further includes a conductive material, and may include an active material, a conductive material, and a binder.
[0052] The conductive material is not particularly limited as long as it has conductivity without causing a chemical change in the battery, and examples thereof include graphite such as natural graphite and artificial graphite; carbon-based substances such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; needle-shaped or branch-shaped conductive whiskers such as zinc oxide whiskers, calcium carbonate whiskers, titanium dioxide whiskers, silicon oxide whiskers, silicon carbide whiskers, aluminum borate whiskers, magnesium borate whiskers, potassium titanate whiskers, silicon nitride whiskers, silicon carbide whiskers, and alumina whiskers; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives. Among these, one type alone or a mixture of two or more types can be used. Specifically, in order to uniformly mix the conductive material and improve conductivity, the conductive material may contain one or more selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes, and more specifically, activated carbon may be included.
[0053] The binder may include a fluorine-containing binder, a non-fluorine-containing binder, or two or more of them. The fluorine-containing binder may be a fluorine-containing polymer, and may include polytetrafluoroethylene (PTFE) and a PVdF-based copolymer such as PVdF (polyvinylidene fluoride) and PVdF-HFP (polyvinylidene fluoride-co-hexafluoropropylene), or two or more of them. Specifically, the fluorine-containing binder may include polytetrafluoroethylene (PTFE). The fluorine-containing binder may include polytetrafluoroethylene alone, or may further include one or more of a PVdF-based copolymer such as PVdF (polyvinylidene fluoride) and PVdF-HFP (polyvinylidene fluoride-co-hexafluoropropylene) in addition to polytetrafluoroethylene. The non-fluorine-containing binder may include polyolefin, polyethylene oxide (PEO), etc.
[0054] According to one embodiment of the present invention, the binder can be fibrous to bind the active material, and when the electrode layer further includes a conductive material, the binder can be fibrous to bind the active material and the conductive material.
[0055] The electrode may contain a fiberized binder as a means for binding the active material or the active material and the conductive material, and such a fiberized binder is less likely to break than a conventional non-fiberized binder and has excellent extensibility in the longitudinal direction, so that the flexibility of the electrode layer and the electrode itself including the same can be improved. The fiberization process of the binder will be specifically discussed in the manufacturing method of the electrode described later.
[0056] According to an embodiment of the present invention, the content of the active material may be 85 to 98 parts by weight, the content of the conductive material may be 0.5 to 5 parts by weight, and the content of the binder may be 0.5 to 10 parts by weight.
[0057] Also, the content of the active material may be 90 to 98 parts by weight, the content of the conductive material may be 0.5 to 5 parts by weight, and the content of the binder may be 0.5 to 5 parts by weight.
[0058] When the contents of the active material, conductive material, and binder satisfy these ranges, the binder can be sufficiently fibrousized in a subsequent kneading process to form a mixture mass, the mixed powder formed in the pulverization process can be molded to easily produce an electrode film, the physical properties of the electrode film can be ensured, and the content of the active material can be ensured, thereby preventing the problem of capacity reduction and ensuring sufficient conductivity.
[0059] On the other hand, in some cases, a filler, which is a component that suppresses the expansion of the electrode, can be further added to the electrode layer. The filler is not particularly limited as long as it is a fibrous material that does not cause chemical changes in the battery, and for example, olefin polymers such as polyethylene and polypropylene, and fibrous substances such as glass fiber and carbon fiber are used.
[0060] The current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and examples of the current collector include stainless steel, aluminum, nickel, titanium, baked carbon, copper, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. The current collector can also have minute irregularities formed on its surface to improve the adhesive strength of the positive electrode active material, and can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0061] Furthermore, the current collector may be entirely or partially coated with a conductive primer layer for reducing surface resistance and improving adhesion. Here, the conductive primer layer may include a conductive material and a binder for the primer layer. The conductive material is not limited as long as it is a material having conductivity, and may be, for example, a carbon-based material, a metal material (metal powder or metal fiber), a conductive whisker, a conductive metal oxide, a conductive polymer, etc. Examples of carbon-based substances include natural graphite, artificial graphite, graphene, carbon black, denka black, acetylene black, ketjen black, super-P, channel black, furnace black, lamp black, thermal black, carbon nanotubes, graphite nanofibers, and carbon nanofibers. Examples of metal substances include copper, nickel, aluminum, and silver. Examples of conductive whiskers include zinc oxide whiskers, calcium carbonate whiskers, titanium dioxide whiskers, silicon oxide whiskers, silicon carbide whiskers, aluminum borate whiskers, magnesium borate whiskers, potassium titanate whiskers, silicon nitride whiskers, silicon carbide whiskers, and alumina whiskers. Examples of conductive metal oxides include titanium oxide. Examples of conductive polymers include polyphenylene derivatives. These can be used alone or as a mixture of two or more types.
[0062] The binder for the primer layer is a solvent-soluble fluorine-based binder (including PVDF and PVDF copolymers) or an acrylic binder, and may include a water-based binder such as styrene butadiene rubber (SBR).
[0063] The single-sided electrode comprises a current collector and an electrode layer on only one side of the current collector, the electrode layer having a porosity of 30% or less. According to one embodiment of the invention, the porosity of the electrode layer of the single-sided electrode can be 20 to 30%, or 22 to 30%, or 23 to 30%, or 25 to 30%, or 26 to 30%, or 26 to 29.4%, or 26 to 28.8%, or 26 to 27%, or 27 to 30%, or 27 to 29.4%, or 27 to 28.8%.
[0064] When the porosity of the electrode layer of the single-sided electrode is 30% or less, the electrolyte impregnation is improved, resulting in excellent life characteristics and output characteristics, and since there is no need to increase the volume to achieve the same capacity, the energy density per volume is improved.
[0065] The porosity of the electrode layer can be calculated by the following equation using the actual density calculated based on the actual density and composition of each component by measuring the apparent density of only the composite film by subtracting the volume and weight of the current collector from the volume and weight of the electrode. Porosity (%) = {1-(apparent density / actual density)} x 100
[0066] According to one embodiment of the present invention, the difference between the porosity of the electrode layer of the single-sided electrode and the porosity of the electrode layer of the other electrode opposite the single-sided electrode may be 5% or less, or 1% to 5%, or 2% to 5%.
[0067] In this case, when the electrode assembly includes a mono-cell group, a single-sided electrode, and a separator interposed between the mono-cell group and the single-sided electrode, the other electrode facing the single-sided electrode may refer to the outermost electrode of the mono-cell group that corresponds to the single-sided electrode and the separator sandwiched therebetween.
[0068] In addition, when the electrode assembly includes a mono-cell group, a single-sided electrode, a half-cell (double-sided electrode) interposed between the mono-cell group and the single-sided electrode, and a separation membrane interposed between each of the mono-cell group, the single-sided electrode, and the half-cell, the other electrode facing the single-sided electrode may refer to an electrode of a half-cell (double-sided electrode) that corresponds to the single-sided electrode and the separation membrane therebetween.
[0069] When the difference between the porosity of the electrode layer of the single-sided electrode and the porosity of the electrode layer of the other electrode facing the single-sided electrode is controlled to 5% or less, the closer the difference in porosity of the single-sided electrode is to the porosity of the other electrode facing the single-sided electrode, i.e., the double-sided electrode, the more advantageous it is in terms of capacity and performance, and in the case of a single-sided electrode having curl characteristics in consideration of processability alone, the porosity can be controlled to be about 5% higher than that of a double-sided electrode. To this end, in one embodiment of the present invention, the single-sided electrode located at the outermost portion of the electrode assembly can have a porosity as similar as possible to that of the double-sided electrode, i.e., a porosity difference of 5% or less.
[0070] The curl of the single-sided electrode is 30 mm or less. According to an embodiment of the present invention, the curl of the single-sided electrode may be 0 mm or more, 1 mm or more, 2 mm or more, 5 mm or more, 8 mm or more, 30 mm or less, 20 mm or less, 18 mm or less, or 8 mm or less, and more specifically, 0 to 30 mm, or 1 to 30 mm, or 2 to 20 mm, 5 to 18 mm, 5 to 8 mm, or 8 to 18 mm, 0 to 18 mm, or 0 to 8 mm, or 0 to 5 mm. When the curl of the single-sided electrode is 30 mm or less, even if such a single-sided electrode is disposed at the outermost part of an electrode assembly, no bending occurs, and thus advantageous effects such as no defects occurring during the assembly process are exhibited. On the other hand, if the curl of the single-sided electrode exceeds 30 mm, the uncoated portion (current collector area where no electrode layer is formed) of the single-sided electrode may be rolled in during the electrode assembly process, or tears may occur at the interface between the uncoated portion and the coated portion (current collector area where an electrode layer is formed), resulting in a high possibility of fracture.
[0071] The curl of the single-sided electrode can be defined as the maximum height of the single-sided electrode after placing the single-sided electrode on a flat reference surface such that the electrode layer of the single-sided electrode faces the flat reference surface and measuring the height of both edges of the single-sided electrode from the reference surface in mm using a ruler.
[0072] In one embodiment of the present invention, the crystallinity of the binder in the electrode layer may be 10% or less.
[0073] In the present invention, the crystallinity (Xc) can be measured by a differential scanning calorimetry (DSC) and is based on the temperature (peak temperature) at the point where the highest enthalpy is shown during crystallization. Specifically, the crystallinity is expressed as a percentage by dividing the melting enthalpy (β value) actually measured by DSC by the melting enthalpy (β equilibrium melting heat) value of a theoretical perfect crystal (crystallinity 100%), and can be calculated by the following Relational Formula 1. Here, the melting enthalpy value of a theoretical perfect crystal can be found and used in the Polymer Handbook for known polymers, and for unknown or newly synthesized materials, it can be calculated by an extrapolation method in which the crystallinity is determined by extending two or more points. [Equation 1] Xc(%)=(β m / β m 0 ) x 100
[0074] According to an embodiment of the present invention, the binder may include a fluorine-containing binder, and the electrode layer may have a Quantified Binder Ratio (QBR) of 1.1 or less.
[0075] The QBR is defined by the following formula: QBR=Bs / Bf
[0076] In the above formula, Bs represents the average value of the fluorine content in a surface region of the electrode layer extending from the outermost surface of the electrode layer to within 15% of the total thickness of the electrode layer, and Bf represents the average value of the fluorine content in a bottom region of the electrode layer extending from the interface of the electrode layer facing the current collector to within 15% of the total thickness of the electrode layer.
[0077] Fig. 1 is a schematic diagram of an electrode according to an embodiment of the present invention. Referring to Fig. 1, an electrode 10 includes an electrode current collector 12 and an electrode layer 11 disposed on the electrode current collector 12 and including an active material and a binder. At this time, the electrode layer may optionally further include a conductive material.
[0078] The electrode layer 11 has a surface region 11s of the electrode layer that extends from the outermost surface of the electrode layer to within 15% of the total thickness d of the electrode layer, and a bottom region 11f of the electrode layer that extends from the interface of the electrode layer facing the current collector to within 15% of the total thickness d of the electrode layer, based on a total thickness d.
[0079] In the above formula QBR, Bs means the average value of the fluorine content in the surface region 11s of the electrode layer, and Bf means the average value of the fluorine content in the bottom region 11f of the electrode layer.
[0080] In this case, the QBR can be calculated as follows:
[0081] First, select the electrode for which you want to check the QBR, and prepare a cross section of the selected electrode using Ar ion milling.Then, use an Energy Dispersive X-ray Spectroscopy (EDS) detector in a Scanning Electron Microscope (SEM) device to perform EDS mapping of the components in the electrode layer of the prepared electrode cross section.
[0082] From the EDS mapping results, a line profile is extracted in the thickness direction of the electrode layer. From the extracted line profile results, the average fluorine content in the surface region of the electrode layer (Bs) and the average fluorine content in the bottom region of the electrode layer (Bf) are extracted, and the QBR value is calculated using the following formula. QBR=Bs / Bf
[0083] In this case, the surface region of the electrode layer is the region from the outermost surface in the thickness direction of the electrode layer to within 15% of the total thickness of the electrode layer, and the bottom region of the electrode layer is the region from the interface of the electrode layer facing the current collector to within 15% of the total thickness of the electrode layer.
[0084] Fig. 2 is a schematic diagram for calculating the QBR value of the electrode layer. Referring to Fig. 2, the X-axis indicates the thickness of the electrode layer, i.e., the distance from the surface toward the current collector, and the Y-axis indicates the intensity of the fluorine component. Line A indicates the intensity of the fluorine component of the fluorine-containing binder extracted by EDS mapping of the fluorine component in the electrode layer of the electrode cross section, and line B is a trend line showing the tendency of line A, which is a line smoothed by the LOWESS smoothing method, i.e., a locally weighted scatterplot smoother method.
[0085] The QBR value is a value indicating the uniformity of the distribution of the fluorine-containing binder in the thickness direction in the electrode layer according to the ratio of the content of the fluorine-containing binder contained in the surface region to the content of the fluorine-containing binder contained in the bottom region of the electrode layer. Here, the content of the fluorine-containing binder can be estimated based on the fluorine component contained in the fluorine-containing binder used.
[0086] The QBR value is less than or equal to 1.1, and according to one embodiment of the present invention, the QBR value can be greater than or equal to 0.95, greater than or equal to 0.97, less than or equal to 1.03, less than or equal to 1.05, and can be between 0.95 and 1.05.
[0087] When the QBR value satisfies the range of 1.1 or less, the problem of the fluorine-containing binder migrating to the surface of the electrode and the content of the fluorine-containing binder contained in the surface region being higher than the content of the fluorine-containing binder contained in the bottom region of the electrode layer does not occur. As a result, the distribution of the binder in the thickness direction of the electrode layer becomes uniform and the binder content in the portion close to the current collector does not decrease, so that the adhesive strength between the current collector and the electrode layer is improved, and the electrical conductivity on the surface of the electrode layer and the charge / discharge rate therefor can also be improved.
[0088] Specifically, the fluorine-containing binder may include polytetrafluoroethylene (PTFE), a PVdF-based copolymer such as PVdF (polyvinylidene fluoride), PVdF-HFP (polyvinylidene fluoride-co-hexafluoropropylene), or two or more of these. Also, the fluorine-containing binder may include polytetrafluoroethylene alone, or may further include one or more of PVdF-based copolymers such as PVdF (polyvinylidene fluoride), PVdF-HFP (polyvinylidene fluoride-co-hexafluoropropylene) in addition to polytetrafluoroethylene.
[0089] The electrode layer may be derived from a film for a dry electrode. The film for a dry electrode refers to a film manufactured by a dry manufacturing method that does not use a dispersion medium, unlike a wet electrode manufacturing method in which an active material and a binder (which may further include a conductive material) are dissolved and / or dispersed in a dispersion medium such as water or an organic solvent, the resulting slurry is applied onto a current collector, and then dried. The electrode film manufactured in this manner is then laminated onto a current collector to finally manufacture an electrode. Specific methods for manufacturing the film for an electrode and the electrode will be described below.
[0090] According to one embodiment of the present invention, the single-sided electrode can be manufactured by a manufacturing method including the steps of: preparing a mixture containing an active material and a binder; kneading the mixture at a temperature in the range of 70° C. to 200° C. under a pressure equal to or higher than normal pressure to prepare a mixture lump; pulverizing the mixture lump to obtain a mixed powder for an electrode; feeding the mixed powder for an electrode between a plurality of rolls and calendering it to form a film for an electrode; and laminating the film for an electrode on a current collector.
[0091] Hereinafter, a method for manufacturing a single-sided electrode applied to an electrode assembly according to the present invention will be described in more detail. According to an embodiment of the present invention, a double-sided electrode included in a mono-cell group or a half-cell, in addition to the single-sided electrode applied to an electrode assembly according to the present invention, may also be manufactured by the following method.
[0092] First, a mixture containing an active material and a binder is prepared. As described above, a conductive material may be optionally further included, and even if a conductive material is not explicitly stated below, an embodiment in which a conductive material is further included will be described.
[0093] In this case, the mixing for producing the mixture is performed so as to uniformly distribute the active material and the binder, and since they are mixed in powder form, there is no limitation as long as it allows simple mixing of these, and various methods can be used for mixing. However, since the electrode of the present invention is produced by a dry production method that does not use a dispersion medium, the above mixing can be performed by dry mixing, and can be performed by putting the materials into a device such as a blender.
[0094] To ensure uniformity, the mixture may be prepared by mixing in a mixer at 5,000 rpm to 20,000 rpm for 30 seconds to 2 minutes, more specifically at 10,000 rpm to 15,000 rpm for 30 seconds to 1 minute.
[0095] According to one embodiment of the present invention, a super mixer or the like may be used in the mixing step of preparing the mixture, and specifically, a method of mixing using a super mixer at 1,000 to 2,000 rpm for 5 to 10 minutes may be applied.
[0096] The binder can be made into fine fibers by the step of producing the mixed powder. The fine fiberization refers to a process of dividing a polymer into fine particles, and can be performed, for example, by using mechanical shear force. Specific examples of such binders are as described above.
[0097] Next, the mixture is kneaded at a temperature in the range of 70° C. to 200° C. under a pressure equal to or higher than normal pressure to produce a mixture mass.
[0098] In known techniques, high shear mixing such as with a jet mill is performed to fiberize the binder. However, this mixing causes problems such as the active material being atomized and the formed fibers being likely to be cut. In the present invention, the above problems are solved by using a low shear kneading method instead of high shear mixing.
[0099] The kneading method is not limited to a specific method. In a specific embodiment of the present invention, the kneading can be performed by a kneading machine such as a kneader.
[0100] This kneading is a step in which the binder is turned into fibers to bind or connect the active material, or the active material and the conductive material, to form a mixture mass having a solid content of 100%.
[0101] Specifically, the kneading can be controlled at a speed of 10 rpm to 100 rpm. For example, the kneading can be controlled at a speed of 20 rpm or more or 70 rpm or less within the above range. The kneading can be performed for 1 minute to 30 minutes. For example, the kneading can be performed at a speed of 20 rpm to 50 rpm within the above range for 3 minutes to 10 minutes. Meanwhile, the kneading can be controlled at a shear rate in the range of 10 / s to 500 / s. In a specific embodiment of the present invention, the kneading can be performed for 1 minute to 30 minutes, and the shear rate can be controlled in the range of 30 / s to 100 / s.
[0102] Moreover, such a kneading step can be carried out under conditions of high temperature and pressure equal to or greater than atmospheric pressure, and more particularly, under conditions of pressure higher than atmospheric pressure.
[0103] More specifically, the kneading can be carried out at a temperature of the mixture in the range of 70°C to 200°C, specifically, 90°C to 180°C.
[0104] If the temperature is lower than the above range, the binder will not be well fibrous during kneading and will not be well agglomerated during kneading, and film formation will not be easily achieved during calendaring. If the temperature is too high, the binder will be rapidly fibrous, and there will be a risk that the already formed fibers will be cut by excessive shear force. This is not preferable.
[0105] The reaction can also be carried out at atmospheric pressure or higher, or under a pressure of 1 atm to 60 atm, or under a pressure of 1 atm to 30 atm, or under a pressure of 1 atm to 10 atm, or under a pressure of 1 atm to 8 atm, or under a pressure of 1.1 atm to 7 atm, or under a pressure of 1.1 atm to 6 atm.
[0106] When the above pressure range is satisfied, problems such as breakage of the formed fibers or excessive density of the mixture mass due to excessive shear force and pressure can be prevented. That is, according to the present invention, when a low shear mixing process is performed under high temperature and pressure conditions equal to or higher than normal pressure instead of high shear mixing, the intended effect of the present invention can be achieved.
[0107] The mixture mass is then pulverized to obtain a mixed powder for an electrode.
[0108] Specifically, the mixture lump produced by the kneading can be immediately calendered, but in this case, the mixture lump needs to be pressed into a thin film, which may cause a problem that a uniform film cannot be obtained, so according to the present invention, the prepared mixture lump is subjected to the pulverization step. That is, if the mixed powder for an electrode obtained by pulverization is excessively large or agglomerated, bridges may be formed in the calendering process, causing defects in the appearance of the film such as pinholes, or a film having non-uniform surface characteristics may be produced, so a mixed powder for an electrode having a uniform size is obtained by pulverization and then calendered.
[0109] In this case, the grinding step can be carried out using an apparatus such as, but not limited to, a blender or grinder, and the grinding step can be carried out specifically at a speed of 5,000 rpm to 20,000 rpm for 30 seconds to 10 minutes, more specifically, at a speed of 10,000 rpm to 18,000 rpm for 30 seconds to 2 minutes.
[0110] If the above-mentioned grinding speed and time are satisfied, sufficient grinding can be performed to form powder of a size suitable for film formation, and the problem of a large amount of fragments occurring in the mixture mass can be prevented. If necessary, a classification process can be performed to filter out powders that are larger than or smaller than a certain size.
[0111] According to one embodiment of the present invention, a cutter mill, a fine mill, etc. can be used in the pulverizing step. At this time, the cutter mill can be used to roughly pulverize the mixture mass produced by kneading at a speed of 400 to 500 rpm for several seconds to a level of several mm. In addition, the fine mill can be used to uniformly pulverize the roughly pulverized powder to a size below a certain level, and can be used at a speed of 3,000 to 8,000 rpm.
[0112] Next, the electrode mixed powder is placed between a plurality of rolls and calendared to form an electrode film.
[0113] 3A and 3B, in the process 100 for forming an electrode film, a plurality of rolls 110 are arranged at a distance from each other, and the mixed powder 120 for an electrode obtained in the above step is put between adjacent rolls 100, which are rotated in a direction opposite to the rolls 100, whereby the mixed powder 120 is rolled and formed into a sheet or film through a powder sheet step, and then finally obtained as an electrode film having a target thickness by multiple calendering processes.
[0114] According to an embodiment of the present invention, the gap between the rolls in the process of forming the electrode film can be appropriately controlled in consideration of the specifications and physical properties of the electrode film to be manufactured. For example, in FIG 3B, the gap between the second and third rolls and the gap between the fourth and fifth rolls can be controlled to be larger than in FIG 3A.
[0115] Specifically, the calendering may be a step of processing the electrode powder mixture into a film having an average thickness of, for example, 50 μm to 300 μm.
[0116] In this case, the calendering can be performed, for example, by using rolls disposed opposite to each other. According to one embodiment of the present invention, the calendering can be performed repeatedly one or more times, for example, 1 to 5 times, or 3 to 4 times, or 4 times.
[0117] At this time, the roll temperature may be from 50°C to 200°C.
[0118] The rotation speed ratio of the rolls can be appropriately controlled depending on the size of the rolls, the number of times of calendaring, and the thickness of the electrode film, and can be controlled within the range of, for example, 1 to 10 times, 1 to 8 times, 1 to 7 times, or 1.2 to 5 times.
[0119] In addition, the distance (gap) between the pair of opposing rolls can be variably adjusted depending on the desired thickness and density of the film.
[0120] Specifically, narrowing the gap between the pair of opposing rolls increases the pressure, whereas widening the gap decreases the pressure. The gap between the pair of opposing rolls may vary depending on the thickness of the film, tolerance of the device, etc., so it may be more appropriate to express it as a force applied to a given length or area.
[0121] According to one embodiment of the present invention, the force exerted by the pair of opposing rolls may be 100 to 500 kgf, or 150 to 450 kgf, or 170 to 300 kgf, or 170 to 250 kgf, or 180 to 230 kgfg per cm of roll width.
[0122] When the process proceeds to the calendering step, a film for a dry electrode that serves as an electrode mixture can be manufactured. Such a film for a dry electrode is also known as a free standing film.
[0123] The electrode film thus produced does not contain a solvent and therefore has almost no fluidity, is easy to handle, and can be processed into a desired shape for use in the production of electrodes of various shapes. In addition, when the electrode film of the present invention is used in the production of an electrode, the drying step for removing the solvent can be omitted, which not only significantly improves the efficiency of the electrode production process but also solves problems such as the breaking of the active material and the breakage of the fibrous binder contained therein, which have been problems in the production of existing dry electrodes.
[0124] Meanwhile, in one embodiment of the present invention, the porosity of the electrode film may be 20% to 35%, or 20% to 33%. In order to roll an electrode film having a porosity of more than 35% to a porosity of 30% or less of the electrode layer of a single-sided electrode or a double-sided electrode finally obtained through a lamination step, a high pressure is required, and during the rolling process, defects such as curling may occur in the case of a single-sided electrode, and wrinkles and overlaps in the uncoated area may occur in the case of a double-sided electrode. In one embodiment of the present invention, if the porosity of the electrode film satisfies the range of 20% to 35%, such problems can be prevented. In one embodiment of the present invention, the porosity can be calculated by the following formula using the actual density calculated based on the actual density and composition of each component by measuring the apparent density of the electrode film. Porosity (%) = {1-(apparent density / actual density)} x 100
[0125] Next, the electrode film is laminated onto a metal current collector.
[0126] The lamination step may be a step of rolling and attaching the electrode film obtained in the above step to a current collector at a predetermined thickness. The lamination may also be performed by a lamination roll, and the lamination roll may be maintained at a temperature of 25 to 250°C.
[0127] According to one embodiment of the present invention, the compression ratio of the electrode film may be from 30 to 50%, or from 35 to 50%, or from 40 to 50%.
[0128] The compression ratio of the electrode film can be defined as the ratio of the thickness to which the electrode film is compressed at the moment of lamination, and can be expressed by the following formula 1. [Formula 1] Compression ratio (%) = T p / T1×100
[0129] In Equation 1, T p means the pressed thickness of the electrode film in the lamination step, and T1 means the thickness of the electrode film before the lamination step is performed.
[0130] In the present invention, by adjusting the compression ratio in the lamination step to satisfy a specific range, it is possible to provide an appropriate density and porosity of the electrode film and excellent adhesion between the electrode film and the current collector.
[0131] When the compression ratio of the electrode film is in the range of 30 to 50%, the pressure applied to the electrode film is sufficient, and the adhesive strength between the electrode film and the current collector is improved, so that the electrode film can be prevented from peeling off from the current collector after the lamination process, and the density of the electrode film can be increased more than necessary to exhibit a porosity lower than the target porosity or to solve the problem of the current collector being damaged.
[0132] In one embodiment of the present invention, when an electrode film is laminated on both sides of the current collector, the compression ratio (%) in the above formula 1 may be expressed by the following formula 2: [Formula 2] 30≦(T1+0.5T c -0.5T gap ) / T1×100≦50
[0133] In Equation 2, T1 means the thickness of the electrode film before the lamination step, and T c means the thickness of the current collector, and T gap means the distance between the first and second rolls.
[0134] In addition, the rolling ratio of the electrode film subjected to the lamination step during the production of the double-sided electrode may be in the range of 20% or less, or 18% or less, or 15% or less, or 5% to 15%, or 6% to 15%, or 7% to 15%, or 9% to 13%.
[0135] The rolling ratio of the electrode film subjected to the lamination step in the manufacture of a single-sided electrode according to one embodiment of the present invention may be in the range of 10% or less, or 3% to 10%, or 3.5% to 10%, or 3.7% to 7.1%, or 3.7% to 4.9%, or 4.9% to 7.1%.
[0136] Here, the rolling ratio can be defined as the ratio of the thickness of the electrode film after the lamination step to the thickness of the electrode film before the lamination step, and can be expressed by the following formula 3. [Formula 3] Rolling ratio (%) = (T1-T2) / T1 x 100
[0137] In the above formula 3, T1 means the thickness of the electrode film before the lamination step, and T2 means the thickness of the electrode film after the lamination step.
[0138] When the rolling ratio satisfies the above-mentioned range, appropriate density and porosity of the electrode film, and adhesive strength between the electrode film and the current collector can be achieved.
[0139] The increase rate of the apparent density before and after lamination of the electrode film with the current collector can be expressed by the following formula 4. [Formula 4] Appearance density increase rate (%) = (D2-D1) / D1 x 100
[0140] D1 is the apparent density (g / cm) of the electrode film before the lamination step. 3 ) and D2 is the apparent density (g / cm ) of the electrode film after the lamination step. 3 ) is shown.
[0141] The increase rate of the appearance density before and after lamination with the current collector of the film for the electrode can be 5 to 30%, or 7 to 25%, or 10 to 20%.
[0142] D1 and D2 indicating the appearance density of the film for the electrode can be variously changed depending on the type of the active material. According to one embodiment of the present invention, when the active material is lithium nickel-manganese-cobalt oxide Li 1+x (Ni a Co b Mn c ) 1-x O2 (x = 0 to 0.03, a = 0.3 to 0.95, b = 0.01 to 0.35, c = 0.01 to 0.5, a + b + c = 1), or an oxide in which a part of lithium nickel-manganese-cobalt oxide is substituted with aluminum (lithium nickel-manganese-cobalt-aluminum oxide) Li a [Ni b Co c Mn d Al e 1-f M 1 f O2 (wherein the M 1 is one or more selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S, 0.8 ≦ a ≦ 1.2, 0.5 ≦ b ≦ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≦ e ≦ 0.1, 0 ≦ f ≦ 0.1), etc., the D1 and D2 can be in the range of 2.75 g / cm 3 to 3.8 g / cm 3 .
[0143] On the other hand, when the increase rate of the appearance density of the film for the electrode satisfies the above range, the adhesive force between the film for the electrode and the current collector can be improved, and problems such as the porosity deviating from the target range or the active material or the current collector being damaged can be prevented.
[0144] The apparent density of the electrode film before and after lamination with the current collector can be calculated by measuring the weight and thickness of the electrode film before lamination, measuring the weight and thickness of the electrode after lamination, and subtracting the weight and thickness of the current collector to determine the weight and thickness of the film.
[0145] The active material loading of the electrode film is 3 mAh / cm 2 to 15mAh / cm 2 For details, see 4mAh / cm 2 to 10mAh / cm 2 It could be.
[0146] Here, the loading amount of the active material is a value calculated by the following formula 5. [Formula 5] Active material loading (mAh / cm 2 ) = Capacity of active material (mAh / g) × Weight content ratio of active material in dry electrode film (wt%) × Weight per unit area of dry electrode film (g / cm 2 )
[0147] In addition, the interface resistance between the electrode film and the current collector is 5 Ω cm 2 For details, see below: 2Ω·cm 2 Here, the interfacial resistance can be calculated by applying a current of 100 μA to the electrode using a multi-probe (MP) resistance measurement method and measuring the resistance between the film for dry electrode and the current collector layer according to the potential difference measured between multiple probes. If the interfacial resistance range is satisfied, the battery performance of a secondary battery manufactured thereafter can be improved.
[0148] 4 is a schematic diagram of a step of laminating an electrode film on both sides of a current collector in a double-sided electrode applied to an electrode assembly according to an embodiment of the present invention. That is, in the laminating step (200), the electrode film 230 obtained in the above step is rolled and attached to a current collector 220 at a predetermined thickness using a pair of laminating rolls 210 to finally obtain an electrode 240.
[0149] 5 is a schematic diagram of a step of laminating an electrode film on one side of a current collector in a single-sided electrode applied to an electrode assembly according to an embodiment of the present invention. That is, in the laminating step (200), the electrode film 230 obtained in the above step is rolled and attached to a current collector 220 at a predetermined thickness using a pair of laminating rolls 210 to finally obtain an electrode 240.
[0150] According to one aspect of the present invention, there is provided a secondary battery including the electrode assembly according to the embodiment of the present invention described above. A secondary battery in which the electrode assembly is incorporated in a battery case (cylindrical case, prismatic case, pouch, etc.) together with a lithium-containing non-aqueous electrolyte, and an energy storage device including the same as a unit battery are also provided.
[0151] At this time, since the specific structures of the secondary battery and the energy storage device are well known, the description thereof will be omitted in this specification.
[0152] Meanwhile, according to one embodiment of the present invention, there is provided a manufacturing apparatus for implementing the above-mentioned method for manufacturing a unit electrode or a double-sided electrode, the dry electrode manufacturing apparatus including a blender for mixing raw materials for a composite including an active material, a binder, and (optionally further including a conductive material), a kneader for kneading the mixture to manufacture a mixture mass, a pulverizer for pulverizing the mixture mass to form a mixed powder for an electrode, a calendar for forming the mixed powder for an electrode into a film for a dry electrode, and a lamination roll for disposing the film for a dry electrode on at least one side of a current collector and laminating it.
[0153] The blender is a mixer for mixing raw materials, and as described above, can mix the raw materials of the combination at a speed of 5000 rpm to 20000 rpm. As the mixer, a super mixer or the like can be used.
[0154] The kneader is a device for fiberizing the binder and dispersing the raw materials of the composite material in the present invention, and the mixture can be obtained as a mixture mass by kneading with the kneader. At this time, the kneading for obtaining the results according to the present invention can be performed at a temperature range of 70°C to 200°C or 90°C to 180°C and at a pressure of normal pressure or higher, or 1 atm to 60 atm, or 1 atm to 30 atm, or 1 atm to 10 atm, or 1 atm to 8 atm, or 1.1 atm to 7 atm, or 1.1 atm to 6 atm.
[0155] The pulverizer is a device for pulverizing the mixture mass to form a mixed powder for an electrode, and a blender or grinder can be used for this purpose. Examples of the grinder include a cutter mill and a fine mill.
[0156] The calender is a device for forming the electrode powder mixture into a film, and is, for example, a pair of rollers facing each other, and the thickness of the film can be adjusted by adjusting the distance between them.
[0157] The laminating roll serves to attach and roll the film for a dry electrode formed by the calendar onto at least one surface of a current collector.
[0158] By using such a calendar and laminating roll, the porosity of the film for a dry electrode according to the present invention can be determined.
[0159] That is, the dry electrode manufacturing apparatus according to the present invention is characterized by including a kneader and a pulverizer.
[0160] The specific structures of the blender, kneader, calendar, and laminating roll are conventionally known, and detailed explanations thereof will be omitted in this specification.
[0161] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention can be modified into various other forms, and the scope of the present invention is not limited to the examples described in detail below. The embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.
[0162] Example 1 (1) Manufacturing of single-sided positive electrodes Lithium nickel cobalt manganese aluminum oxide (NCMA, Li[Ni 0.87 Co 0.05 Mn 0.07 Al 0.01 960 g of PO2), 10 g of carbon black as a conductive material, and 30 g of polytetrafluoroethylene (PTFE) as a binder were placed in a blender and mixed at 10,000 rpm for 1 minute to prepare a mixture, which was then placed in the kneader.
[0163] The kneader temperature was stabilized at 150°C, and the mixture was placed in the kneader, and the lid was operated at a speed of 40 rpm for 5 minutes under a pressure of 1.1 atmospheres (atm) to obtain a mixture mass. The mixture mass was put into a blender, pulverized at 10,000 rpm for 30 seconds, and classified using a sieve with a pore size of 1 mm to obtain a mixed powder for electrodes. The produced mixed powder for electrodes was then put into a wrap calendar (roll diameter: 160 mm, roll temperature: 100°C) three times to produce a film for electrodes. By adjusting the gap during the calendaring process, a film for electrodes having the desired density (porosity) could be produced.
[0164] At this time, by adjusting the pressing force of the calendaring process, a film for a dry electrode having a desired porosity could be produced. The pressure applied by a pair of opposing rolls during the calendaring process was 221 kgf per cm of film width.
[0165] One sheet of the electrode film was placed on one side of a current collector (aluminum foil (thickness 15 μm) coated with a conductive primer layer of 0.5 μm on both sides, which was a mixture of carbon black and PVDF binder in a weight ratio of 1:2), and laminated using a room temperature compression roll (lamination roll) to prepare a single-sided positive electrode.
[0166] The lamination conditions were that the diameter of the pair of opposing compression rolls was 200 pi, the peripheral speed ratio of the pair of compression rolls was 1:1, and the force applied by the compression rolls was 155 kgf per cm of film width.
[0167] At this time, the thickness, porosity, and loading of the electrode film before the lamination step, the rolling ratio in the lamination step, and the thickness, porosity, and loading of the electrode layer provided on one side of the current collector after the lamination step are shown in Table 1.
[0168] (2) Manufacturing of electrode assemblies 1) Manufacturing of double-sided negative electrodes A negative electrode mixture was prepared by mixing 97.6 parts by weight of artificial graphite and natural graphite (weight ratio: 90:10) as the negative electrode active material, 1.2 parts by weight of styrene butadiene rubber (SBR) functioning as a binder, and 1.2 parts by weight of carboxymethyl cellulose (CMC). A negative electrode mixture slurry was prepared by dispersing this negative electrode mixture in ion-exchanged water functioning as a solvent. This slurry was coated on both sides of a 20 μm thick copper foil, dried, and pressed to produce a double-sided negative electrode.
[0169] 2) Manufacturing of double-sided positive electrodes A double-sided positive electrode was manufactured by the same manufacturing process as the single-sided positive electrode, except that in the manufacturing step of the single-sided positive electrode, two electrode films were placed on both sides of the current collector and laminated. At this time, the load of the double-sided electrode was 5.0 mAh / cm. 2 The porosity of the electrode layer was 26%.
[0170] 3) Manufacturing of electrode assemblies An electrode assembly was manufactured by stacking the prepared single-sided positive electrode, double-sided negative electrode, and double-sided positive electrode with a polyethylene film (thickness: 9 μm) as a separator in the order of single-sided positive electrode / separator / double-sided negative electrode / separator / double-sided positive electrode / separator / double-sided negative electrode / separator / double-sided positive electrode / separator / double-sided negative electrode / separator / double-sided positive electrode / separator / double-sided negative electrode / separator / double-sided positive electrode / separator / double-sided negative electrode.
[0171] Example 2 A single-sided positive electrode and an electrode assembly were manufactured in the same manner as in Example 1, except that the thickness, porosity, and loading of the electrode film before the lamination step, the rolling ratio in the lamination step, and the thickness, porosity, and loading of the electrode layer provided on one side of the current collector after the lamination step were set to the conditions shown in Table 1.
[0172] At this time, the pressure of the calendaring process was adjusted to produce a film for a dry electrode having a desired porosity. The pressure applied by a pair of opposing rolls during the calendaring process was 170 kgf per cm of film width.
[0173] The lamination conditions were that the diameter of the pair of opposing compression rolls was 200 pi, the peripheral speed ratio of the pair of compression rolls was 1:1, and the force applied by the compression rolls was 257 kgf per cm of film width.
[0174] Example 3 A single-sided positive electrode and an electrode assembly were manufactured in the same manner as in Example 1, except that the thickness, porosity, and loading of the electrode film before the lamination step, the rolling ratio in the lamination step, and the thickness, porosity, and loading of the electrode layer provided on one side of the current collector after the lamination step were set to the conditions shown in Table 1.
[0175] At this time, the pressure of the calendaring process was adjusted to produce a film for a dry electrode having the desired porosity. The pressure applied by a pair of opposing rolls during the calendaring process was 264 kgf per cm of film width.
[0176] The lamination conditions were as follows: the diameter of the pair of opposing compression rolls was 200 pi, the peripheral speed ratio of the pair of compression rolls was 1:1, and the force applied by the compression rolls was 190 kgf per cm of film width.
[0177] Example 4 A single-sided positive electrode and an electrode assembly were manufactured in the same manner as in Example 1, except that the thickness, porosity, and loading of the electrode film before the lamination step, the rolling ratio in the lamination step, and the thickness, porosity, and loading of the electrode layer provided on one side of the current collector after the lamination step were set to the conditions shown in Table 1.
[0178] At this time, the pressure of the calendaring process was adjusted to produce a film for a dry electrode having a desired porosity. The pressure applied by a pair of opposing rolls during the calendaring process was 386 kgf per cm of film width.
[0179] The lamination conditions were as follows: the diameter of the pair of opposing compression rolls was 200 pi, the peripheral speed ratio of the pair of compression rolls was 1:1, and the force applied by the compression rolls was 85 kgf per cm of film width.
[0180] Comparative Example 1 A single-sided positive electrode and an electrode assembly were manufactured in the same manner as in Example 1, except that the thickness, porosity, and loading of the electrode film before the lamination step, the rolling ratio in the lamination step, and the thickness, porosity, and loading of the electrode layer provided on one side of the current collector after the lamination step were set to the conditions shown in Table 1.
[0181] At this time, the pressure applied by the pair of opposing rolls during the calendaring process was adjusted to produce a film for a dry electrode having the desired porosity. At this time, the pressure applied by the pair of opposing rolls during the calendaring process was 130 kgf per cm of film width.
[0182] The lamination conditions were as follows: the diameter of the pair of opposing compression rolls was 200 pi, the peripheral speed ratio of the pair of compression rolls was 1:1, and the force applied by the compression rolls was 575 kgf per cm of film width.
[0183] Comparative Example 2 A single-sided positive electrode and an electrode assembly were manufactured in the same manner as in Example 1, except that the thickness, porosity, and loading of the electrode film before the lamination step, the rolling ratio in the lamination step, and the thickness, porosity, and loading of the electrode layer provided on one side of the current collector after the lamination step were set to the conditions shown in Table 1.
[0184] At this time, the pressure applied by the pair of opposing rolls during the calendaring process was adjusted to produce a film for a dry electrode having the desired porosity. At this time, the pressure applied by the pair of opposing rolls during the calendaring process was 112 kgf per cm of film width.
[0185] The lamination conditions were as follows: the diameter of the pair of opposing compression rolls was 200 pi, the peripheral speed ratio of the pair of compression rolls was 1:1, and the force applied by the compression rolls was 210 kgf per cm of film width.
[0186] Performance evaluation The single-sided electrodes (positive electrodes) constituting the electrode assemblies manufactured in Examples 1 to 4 and Comparative Examples 1 and 2 were evaluated as follows. The results are shown in Table 1.
[0187] (1) Thickness The thickness was measured using a thickness gauge (Mitutoyo, VL-50S-B).
[0188] (2) Load Amount The load was calculated using the following formula: Load capacity (mAh / cm 2 ) = [Capacity of active material (mAh / g)] × [Weight content ratio of active material in electrode film (wt%)] × [Weight per unit area of electrode film (g / cm 2 )]
[0189] (3) Porosity (%) In this case, the porosity of the electrode was calculated by measuring the apparent density of only the electrode layer by subtracting the volume and weight of the current collector from the volume and weight of the electrode, and the actual density of each component was calculated based on the actual density and composition, and the actual porosity of each electrode was calculated according to the following relational equation. Porosity (%) = {1-(apparent density / actual density)} x 100
[0190] (4) Curling of one-sided electrodes The single-sided electrode was placed on a flat reference surface such that the electrode layer of the single-sided electrode was facing the flat reference surface, and the heights of both edges of the single-sided electrode from the reference surface were measured in mm using a ruler, and the maximum height among these heights was defined as the curl of the single-sided electrode.
[0191] FIG. 9 is a photograph showing the measurement results of curl in the single-sided electrode of Example 2, and FIG. 10 is a photograph showing the measurement results of curl in the single-sided electrode of Comparative Example 1.
[0192] [Table 1]
[0193] Referring to Table 1, it is determined that an electrode assembly having improved curl characteristics can be provided by having the porosity of the electrode layer of the outermost single-sided electrode provided in the electrode assemblies of Examples 1 to 4 being 30% or less, the curl of the single-sided electrode being 30 mm or less, and the energy density being maximized. Meanwhile, in the case of the single-sided electrode applied to the electrode assembly of Comparative Example 1, the curl was severely rolled in, and the curl measurement itself was impossible (NG), and in the case of the single-sided electrode applied to the electrode assembly of Comparative Example 2, the porosity of the electrode layer of the single-sided electrode showed a high value.
Claims
1. a mono-cell group including one or more mono-cells; a single-sided electrode laminated on at least one of the upper and lower outermost sides of the mono-cell group; A separator interposed between the monocell group and a single-sided electrode, The single-sided electrode includes a current collector and an electrode layer on only one side of the current collector, the electrode layer having a porosity of 30% or less; The electrode assembly, wherein the curl of the single-sided electrode is 30 mm or less.
2. The electrode assembly of claim 1 , wherein the group of monocells comprises one monocell or comprises two or more monocells stacked together.
3. The electrode assembly according to claim 1 , further comprising a half cell interposed between the monocell group and the unit electrode.
4. 4. The electrode assembly according to claim 1, wherein a difference between a porosity of the electrode layer of the one-sided electrode and a porosity of an electrode layer of the other electrode facing the one-sided electrode is 5% or less.
5. the single-sided electrode comprises a current collector and an electrode layer located on the current collector and including an active material and a binder; The electrode assembly according to claim 1 , wherein the binder is fiberized to bind the active material.
6. The electrode assembly of claim 5 , wherein the electrode layer comprises an active material, a conductive material, and a binder.
7. The electrode assembly of claim 5 , wherein the binder comprises polytetrafluoroethylene (PTFE).
8. 7. The electrode assembly according to claim 6, wherein the content of the active material is 80 to 98 parts by weight, the content of the conductive material is 0.5 to 10 parts by weight, and the content of the binder is 0.5 to 5 parts by weight.
9. The electrode assembly of claim 5 , wherein the current collector further comprises a conductive primer layer on at least one surface.
10. The electrode assembly of claim 5 , wherein the electrode layer is derived from a dry electrode film.
11. The single-sided electrode is Producing a mixture including an active material and a binder; Kneading the mixture at a temperature in the range of 70° C. to 200° C. under a pressure equal to or higher than normal pressure to produce a mixture mass; pulverizing the mixture mass to obtain a mixed powder for an electrode; The electrode mixed powder is put between a plurality of rolls and calendered to form an electrode film; The electrode assembly according to claim 1 , which is manufactured by a manufacturing method including the step of: laminating the electrode film onto a current collector.
12. The electrode assembly according to claim 11 , wherein the step of kneading to prepare a mixture mass is performed in a kneader under a pressure equal to or higher than atmospheric pressure.
13. The electrode assembly according to claim 11 , wherein the rolling ratio of the electrode film in the laminating step is 10% or less.
14. A secondary battery comprising the electrode assembly according to claim 1.
15. An energy storage device comprising the secondary battery according to claim 14 as a unit battery.
Citation Information
Patent Citations
Laminated battery
JP2007149349A
Lithium ion secondary battery
JP2018014266A
Electrode, secondary battery comprising the same and methode for producing the same, electrode and secondary battery manufactured by the same
KR1020160100863A